PENGEMBANGAN MATERI AJAR PENDIDIKAN AGAMA ISLAM PADA PERGURUAN TINGGI BERBASIS TERJEMAHAN ISTILAH BAHASA ARAB - MIFTAH WANGSADANUREJA (Universitas Muhammadiyah Prof Dr Hamka, 2017)
The course of Islamic Education (PAI) at the Public University (PTU) for its students seems to be merely a science of knowledge insight only and can not be used as ideological identity in their daily life. This can be proved by the time the author goes around the campus area and finds some students they talks with his fellow students using rough language, such as the phrase